2012
DOI: 10.3109/14767058.2011.648239
|View full text |Cite
|
Sign up to set email alerts
|

The creamatocrit, fat and energy concentration in human milk produced by mothers of preterm and term infants

Abstract: The lowest creamatocrit, calories and fat concentration was indicated in the preterm milk obtained in the morning (4.86%, 663.8 kcal/L and 33.6 g/L, respectively). The highest milk parameters were observed in the night samples of full-term milk and measured (9.6%, 919.7 kcal/L, and 60.7 g/L, respectively). No significant differences in analysed parameters were observed between preterm and full-term milk (p>0.05). In summary, creamatocrit, calories and lipid concentration in breast milk shows the daily differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…36,37 Our results are similar to those reported in a previous systematic meta-analysis, 38 in which energy content was approximately 60 kcal/100 mL for colostrum. 39,40 No difference was found between energy content distributions in fresh, refrigerated, and frozen samples (Table 3). 39 For instance, Kociszewska-Najman et al 39 showed energy content values of 66 kcal/100 mL (preterm milk) and 68 kcal/100 mL (term milk) for colostrum samples, 82 kcal/100 mL (preterm) and 83 kcal/100 mL (term) for transitional milk, and 76 kcal/100 mL (preterm) and 85 kcal/100 mL (term) for mature milk.…”
Section: Energy Content Values Were Similar For Fresh and Stored Milkmentioning
confidence: 93%
See 2 more Smart Citations
“…36,37 Our results are similar to those reported in a previous systematic meta-analysis, 38 in which energy content was approximately 60 kcal/100 mL for colostrum. 39,40 No difference was found between energy content distributions in fresh, refrigerated, and frozen samples (Table 3). 39 For instance, Kociszewska-Najman et al 39 showed energy content values of 66 kcal/100 mL (preterm milk) and 68 kcal/100 mL (term milk) for colostrum samples, 82 kcal/100 mL (preterm) and 83 kcal/100 mL (term) for transitional milk, and 76 kcal/100 mL (preterm) and 85 kcal/100 mL (term) for mature milk.…”
Section: Energy Content Values Were Similar For Fresh and Stored Milkmentioning
confidence: 93%
“…36,37 Moreover, the major fraction contributing to energy variation in milk is related to fat and cream content, whereas a constancy of energy contribution has been shown for protein and lactose content in milk. 39 Energy content values may differ in other studies because this measurement is influenced by milk lipid composition, 36,37 which in turn is related to the mother's lactation stage, time of the day when milk was expressed, and repeated expressions for pooled samples. Distinct energy content measurements (based on creamatocrit assessment) may be obtained according to the mother's lactational stage.…”
Section: Energy Content Values Were Similar For Fresh and Stored Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Common practice is to fortify on an assumed average preterm breast milk composition (6,7,9) ; however, significant variation in the macronutrient content of breast milk exists between and within mothers (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) , reflected by wide variations in macronutrient values derived by studies and adopted by neonatal intensive care units and industry to fortify milk, raising concerns that this practice may lead to undernourishment of some infants and over-nourishment of others (7) . The lack of a globally accepted reference 'assumed' preterm breast milk composition inhibits standardised reporting of nutritional intakes, making it difficult for clinicians and researchers to assess the adequacy of nutritional intakes and the role of nutrition in growth and developmental preterm outcomes.…”
mentioning
confidence: 99%
“…An approximation of energy content and lipid content can be performed by creamatocrit (10,(27)(28)(29)(30) . In this study, the range of lipid content is between 20 and 67 g/l, mainly owing to the variations during the day and during lactation (30)(31)(32) ; we tried to minimise this effect by taking the samples at three times of the day, analysing samples twice and by mixing samples to obtain averages over 24 h. Our results are close to the 'normal' lipid content ranges reported from 35 to 45 g/l (33)(34)(35) .…”
Section: Discussionmentioning
confidence: 99%